Poly(A) Polymerase from Vaccinia Virus-Infected Cells I. Partial Purification and Characterization - Brakel, Christine (1974)
Poly(A) polymerase activity is induced during vaccinia virus infection of HeLa cells. The enzyme is maximally induced at 3.5 h postinfection. Partial purification frees the preparation of RNase activity and RNA polymerase activity. ATP is the substrate for poly(A) synthesis. A small amount of poly(A) is produced from added adenosine diphosphate due to the production of ATP by an adenylate kinase present in the preparation. The incorporation of ATP into poly(A) is dependent on divalent cations (Mg(2+) or Mn(2+)) and is not inhibited by UTP, CTP, or GTP. Poly(U) stimulates ATP incorporation; poly(A) and poly(C) have little effect on ATP incorporation, and poly(dT) is extremely inhibitory. RNA prepared from HeLa cells and from the partially purified poly(A) polymerase (the enzyme preparation contains endogenous RNA [Brakel and Kates]) stimulates ATP incorporation by poly(A) polymerase which was subjected to DEAE-cellulose chromatography. RNase's, pancreatic and T(1), inhibit the production of poly(A). DNase has little effect. Poly(U) is able to stimulate poly(A) production in the presence of T(1) RNase.